LEXICAL COHESION USED IN INDONESIAN AND ENGLISH VERSIONS OF LASKAR PELANGI, A NOVEL - HANUM, LULUK LUTFIYA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: cohesion, cohesion devices, lexical cohesion, novelLexical cohesion is a linguistic device which helps to create cohesiveness of the text. One kind of text that has to have cohesiveness is novel. This present study aims to know the types of lexical cohesion used in the Indonesian and English versions of Laskar Pelangi and also the similarities and differences in the use of lexical cohesion in both novels.This study uses mixed approach. Qualitative approach is used to describe the analysis of the lexical cohesion found in the novels. Quantitative approach is used to count the total number and the percentage of the lexical cohesion used in the novels. Document analysis is also used in this study since the data was taken from novel in which it employs text or document.This study reveals that both Indonesian and English versions of Laskar Pelangi novel used all types of lexical cohesion. There are 3 similarities found in the analysis. First, the most frequent types used in both data are repetition and antonymy. Second, the use of synonymy is the same 8%. Third, there is no tautotes found in both data. Moreover, there are 2 differences found in the analysis. First, the frequently used lexical cohesion types in Indonesian are repetition, antonymy, synonymy, collocation, hyponymy, and equivalency, while the English are repetition, antonymy, equivalency, collocation, synonymy, meronymy, and hyponymy. Second, Indonesian version used symploce but the English version did not. After all, lexical cohesion is used to make the writing ortext more cohesive so the readers can easily understand the flow of the story in thenovel.The researcher suggests the English learners to learn more about lexical cohesion to make their writing cohesive. Furthermore, the future researcher can widen the subject and use another object then analyze it using other theories of cohesion.